Vanderbilt : the rise and fall of an American dynasty - Cooper, Anderson; Howe, Katherine, 1977- (Harper, an imprint of HarperCollinsPublishers, 2021)
Drawing on never-before-seen documents and told from a unique insider's viewpoint, the CNN anchor tells the story of his legendary family and their remarkable influence.